Governança pública e compliance: os novos caminhos das contratações públicas - Martins, Murilo Moreira (2019)
This research is available to discuss the need for governance techniques and the application of compliance programs in the scope of Brazilian public contracting. An approach was sought on the importance of the implementation of compliance programs as a new value that goes to govern all the New Public Administration and mainly the public hirings. The analysis also goes through the international guidelines on anti-corruption and the main national legislations dealing with this issue. The objective is to bring greater clarity to the elements needed for a compliance program to be considered efficient. The institutionalization of corporate compliance programs constitutes one of the largest and most forceful cultural changes today in an advanced stage of expansion in the scope of private and public business in Brazil. The adoption of methods and techniques for risk management and prevention of fraudulent practices became the main concern of business practices, reaching the space of laws and public policies especially aimed at preventing, combating and making corruption accountable in public contracting. The research aims to awaken to the need to take a proactive anticorruption stance in the daily dealings between the public and private sectors. All this is linked to the new model of Brazilian Administrative Law, which is increasingly directed towards the protection of the human person and the realization of the fundamental right to good administration.